2018
DOI: 10.1155/2018/5869010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Rainfall Trends and Its Relationship with SST Signals in the Lake Tana Basin, Ethiopia

Abstract: The impacts of climate change and climate variability on human life have led the scientific community to monitor the behavior of weather and climate variables at different spatial and temporal scales. This paper explores seasonal and annual trends of rainfall in the Lake Tana basin (LTB) and their teleconnections with global sea surface temperatures (SSTs) over the period between 1979 and 2015. The nonparametric Mann–Kendall test and Sen’s slope estimate are applied to the rainfall data collected from the Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…The results imply that the DRB is generally becoming more wet, which has positive impacts on agricultural production and water resources availability. The finding is consistent with previous studies that reported the southwestern part of the upper Blue Nile basin, where the DRB is located, is becoming more wetting (e.g., Mellander et al 2013;Brown et al 2017;Weldegerima et al 2018;Worku et al 2018). Moreover, the seasonal shift in rainfall reported in this study is consistent with previous studies for the upper Blue Nile basin (Berhane et al 2014;Vincent et al 2018).…”
Section: Spatiotemporal Climate Trendssupporting
confidence: 93%
“…The results imply that the DRB is generally becoming more wet, which has positive impacts on agricultural production and water resources availability. The finding is consistent with previous studies that reported the southwestern part of the upper Blue Nile basin, where the DRB is located, is becoming more wetting (e.g., Mellander et al 2013;Brown et al 2017;Weldegerima et al 2018;Worku et al 2018). Moreover, the seasonal shift in rainfall reported in this study is consistent with previous studies for the upper Blue Nile basin (Berhane et al 2014;Vincent et al 2018).…”
Section: Spatiotemporal Climate Trendssupporting
confidence: 93%
“…e increasing trend in the rainfall amount in the midland AEZ was in line with recent ndings from Degefu and Bewket [38] in which Wolaita Sodo, as one of the meteorological stations, was found to experience an increasing trend in the average annual total rainfall (p < 0.01). Similarly, a recent study by Weldegerima et al [70] in Northern Ethiopia has documented an increase in annual rainfall with the magnitude of change being 2.20, 3.42, 6.58, and 2.88 mm/year, in Bahir Dar, Dangila, Debre Tabor, and Gondar, respectively. On the contrary, insigni cant decreasing trend was reported both in the lowland and in the highland AEZs in R10mm while it was insigni cant increasing trend in the midland AEZ.…”
Section: Number Of Heavy (R10mm) and Very Heavy (R20mm) Precipitationmentioning
confidence: 61%
“…Several other studies at various spatial and temporal scales have recognized warming trends in maximum temperature [4,20,21,28,63]. On the rate of increase, without adaptation, more than 1°C warming has adverse impacts [3].…”
Section: Variability and Trends In Annual Maximummentioning
confidence: 99%
“…Some attempts have been made on the climate trend analysis in Ethiopia, reporting mixed findings. For example, an insignificant trend was reported on the annual rainfall amount in the Nile basin [15][16][17][18][19][20][21]. Similarly, a nonsignificant trend in annual and seasonal rainfall was reported in Southwestern Ethiopia [22] and North Ethiopia [23].…”
Section: Introductionmentioning
confidence: 99%